Relationship between Islam and the West: From Historical Review to Clash or Cooperation? - Edi Kurniawan (Journal of Islamic Civilization, 2023)
Scholars are divided into two groups in assessing the relationship between Islam and the West. Some see it as a clash, while others propose a tolerance thesis. As a result, there is an ongoing debate. However, this paper will negate both. Therefore, this paperwill contextualize this relationship from a historical standpoint and assess its trajectory. This paper is a literature study that takes the sources from library data. By taking scientific cooperation and conflict, crusades and economic cooperation, imperialismagainst the Islamic world, and tolerance of captive colonialists as examples, this paper shows that the relationship between Islam and the West is not unidirectional but multidirectional. Competition, conflict, and cooperation served both interests simultaneously. The interests of religion, knowledge, politics, economy, and culture before, during, and after colonization made the relationship both competitive, conflicting, and cooperative. Thus, the implication of this article is to refute Huntington’s theory and his critics by some scholars.